2008
DOI: 10.1007/s10880-008-9126-7
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Healthcare Experience, Healthcare Attitudes, and Optimism as Predictors of Adolescents’ Healthcare Behavior

Abstract: Late adolescence and early adulthood is a time when people establish many of their life-style behaviors. Thus, in order to promote optimal health, it is important to identify factors predictive of young adults' healthcare behavior. This study evaluated the relationship between measures of childhood healthcare experience, healthcare attitudes, and optimism with young adults' healthcare behavior in a sample of college students (n = 100). Results suggested that prior healthcare experience, attitudes about healthc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 19 publications
(38 reference statements)
1
27
0
Order By: Relevance
“…Long term, children who have more negative experiences with medical procedures are more likely to grow up into adults who avoid healthcare. (Ayers, et al 2011;Jones, et al 2008;Kennedy, et al 2008;Weisman, et al 1998) that inform clinical understanding (Thorne et al 1997;Thorne et al 2004). …”
Section: Methodsmentioning
confidence: 99%
“…Long term, children who have more negative experiences with medical procedures are more likely to grow up into adults who avoid healthcare. (Ayers, et al 2011;Jones, et al 2008;Kennedy, et al 2008;Weisman, et al 1998) that inform clinical understanding (Thorne et al 1997;Thorne et al 2004). …”
Section: Methodsmentioning
confidence: 99%
“…A high level of dispositional optimism has been associated with better mental and physical health, as well as with more protective practices, and resilience to stressful life events on samples of adults (see Carver et al, 2010;Rasmussen, Scheier, & Greenhouse, 2010 for reviews). Previous studies also showed that dispositional optimism is related to various indices of the adolescents' positive adjustment, such as healthcare attitudes, physical and psychological quality of life, or motivation to pursue their goals (e.g., Jones, DeMore, Cohen, O'Connell, & Jones, 2008;Mannix, Feldman, & Moody, 2009;Huan, Yeo, Ang, & Chong, 2006). Recent research suggests that optimism is a modifiable variable that can be developed in adolescents through certain psychological interventions, becoming a stable personality trait throughout adulthood (Mannix et al, 2009;Tusaie & Patterson, 2006).…”
Section: Dispositional Optimismmentioning
confidence: 97%
“…Optimism is considered a trait with high levels of stability over time (38). Adolescent optimism has been associated with a wide range of outcomes including improved healthcare seeking behaviors and lower levels of substance use, obesity, and depression (39-41). …”
Section: Perspectives On Future Orientation and Their Relationship Tomentioning
confidence: 99%